2017
DOI: 10.21608/ejaj.2017.56200
|View full text |Cite
|
Sign up to set email alerts
|

Phytoparasitic Nematodes Associated with Different Cultivars of Grape Grown in Two Types of Soil in Egypt

Abstract: Survey was conducted in Giza, qualiabia and Behaira governorates of Egypt during 2010-2011 seasons, to study the occurrence and population density phytoparasitic nematodes associated with grapes (Vitis). A total number of 160 soil and root samples were collected from the rhizospher of six grape cultivars Bez-Alanza, Flame seedless, King Ruby, Romy Red, Superior and Thomoson seedless were collected by digging soils to a depth of 32-40 cm with stainless steel halftubes. The results indicated that the present of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…Results showed that among plant-parasitic nematodes infecting grapes, the rootknot nematode, Meloidogyne spp., was more common in 94.5% of all studied soil samples, followed by Xiphinema and Tylenchorhynchus. Mohamed et al (2017) found similar results in the governorates of Giza, Qualiabia and Behaira. Data also showed that the highest plant-parasitic nematodes associated with guava and olive fruit trees were the root-knot nematode, Meloidogyne which was detected in 61.6 and 91.5% of all studued soil samples, respectively, followed by the stunt nematode, Tylenchorhynchus spp., and the spiral nematode, Helicotyleuchus sp.…”
Section: Discussionsupporting
confidence: 71%
“…Results showed that among plant-parasitic nematodes infecting grapes, the rootknot nematode, Meloidogyne spp., was more common in 94.5% of all studied soil samples, followed by Xiphinema and Tylenchorhynchus. Mohamed et al (2017) found similar results in the governorates of Giza, Qualiabia and Behaira. Data also showed that the highest plant-parasitic nematodes associated with guava and olive fruit trees were the root-knot nematode, Meloidogyne which was detected in 61.6 and 91.5% of all studued soil samples, respectively, followed by the stunt nematode, Tylenchorhynchus spp., and the spiral nematode, Helicotyleuchus sp.…”
Section: Discussionsupporting
confidence: 71%
“…21, No.1 (2022) Korayem et al (2014) conducted a survey on the plant parasitic nematodes associated with different plants in North Sinai. Also, Mohamed et al (2017) studied phytoparasitic nematodes associated with different cultivars of grape grown in two types of soil in Egypt. Furthermore, Taha (2018) studied the abundance and distribution of plant parasitic nematodes associated with some different plant hosts including grapes, banana, apples, peach and lemon.…”
Section: Introductionmentioning
confidence: 99%
“…For all surveyed villages, stunt nematode was the first in its general average percentage frequency of occurrence of 29.1% followed by that of root knot nematode (27.3%), stubby nematode (13.9%) and lesion nematode. (12.5%) Mohamed et al (2017). conducted a survey in Giza, Qualiabia and Behaira governorates of Egypt during 2010-2011 seasons, to study the occurrence and population density of phytoparasitic nematodes associated with grapes.…”
mentioning
confidence: 99%
“…It has been estimated that these widespread soil inhabitants cause a yield loss of about 12.3% annually, equivalent to approximately $157 billion dollars [ 3 ]. PPNs have expanded widely in the Egyptian vineyard soils [ 4 ]. Their feeding habit on grapevine roots impairs water and nutrients uptake as well as root and shoot growth, resulting in reduced vine vigor and yield losses [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%